2021
DOI: 10.1017/s1368980021003700
|View full text |Cite
|
Sign up to set email alerts
|

Household-level double burden of malnutrition in Ethiopia: a comparison of Addis Ababa and the rural district of Kersa

Abstract: Objective: To examine the prevalence of and factors associated with different forms of household-level double-burden of malnutrition (DBM) in Ethiopia. Design: We defined DBM using anthropometric measures for adult overweight (body mass index (BMI) ≥25 kg/m2), child stunting (height-for-age Z-score <-2 SD) and overweight (weight-for-height Z-score ≥2 SD). We considered 16 biological, environmental, behavioural, and socio-demographic factors. Their association with DBM forms was assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 44 publications
2
19
1
Order By: Relevance
“…The existence of a double burden of malnutrition in the same household was reported in different low-income settings such as in Bangladesh [ 16 , 70 ], Indonesia [ 37 ], Kenya [ 22 ], Nepal [ 15 ], and India [ 59 ]. Few studies have also reported Ethiopia's household-level double burden of malnutrition [ 11 , 25 , 26 ]. The observed prevalence of DBM was lower than the finding from a study in Nepal, 6.6% [ 15 ], and studies from Bangladesh, 6·3%, [ 70 ] and, 4.9%, [ 71 ].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The existence of a double burden of malnutrition in the same household was reported in different low-income settings such as in Bangladesh [ 16 , 70 ], Indonesia [ 37 ], Kenya [ 22 ], Nepal [ 15 ], and India [ 59 ]. Few studies have also reported Ethiopia's household-level double burden of malnutrition [ 11 , 25 , 26 ]. The observed prevalence of DBM was lower than the finding from a study in Nepal, 6.6% [ 15 ], and studies from Bangladesh, 6·3%, [ 70 ] and, 4.9%, [ 71 ].…”
Section: Discussionmentioning
confidence: 99%
“…This demonstrated that Ethiopia, like other LMICs, is subject to the inevitable consequences of DBM; however, the burden of DBM is still not fully understood [ 25 , 26 ]. So far, a few studies on overweight and undernutrition coexisting at the household level have been reported [ 11 , 25 , 26 , 35 ].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations